Problems of and perspectives on language acquisition - Laiveniece, Diāna (Cambridge Scholars Publishing, 2018)
"This volume brings together a selection of articles about research conducted on language acquisition in the Baltic States, in Latvia and Lithuania; a field which has witnessed massive growth in recent years. It will stimulate the reader to ask questions, think of solutions, argue and propose counterarguments with regards to language acquisitions in this region. The driving force in this field is dialogue and argumentative discussion, not utilitarian notes and advice, and, through detailing a range of views on language acquisition problems and perspectives, this volume achieves that aim."--